2014
DOI: 10.1186/1471-2105-15-288
|View full text |Cite
|
Sign up to set email alerts
|

APTE: identification of indirect read-out A-DNA promoter elements in genomes

Abstract: BackgroundTranscriptional regulation is normally based on the recognition by a transcription factor of a defined base sequence in a process of direct read-out. However, the nucleic acid secondary and tertiary structure can also act as a recognition site for the transcription factor in a process known as indirect read-out, although this is much less understood. We have previously identified such a transcriptional control mechanism in early Xenopus development where the interaction of the transcription factor il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…We have previously shown that the Xenopus gata2 promoter is regulated, at least partially, by an A-form DNA structure (Llewellyn et al 2009;Scarlett et al 2004). A range of genes were identified in a screen to reveal other, similarly regulated targets and our data suggested that the promoter of one of these genes was probably, like gata2, a target for the Ilf3 transcription factor (Whitley et al 2014), here we have described the identification and characterisation of this gene.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We have previously shown that the Xenopus gata2 promoter is regulated, at least partially, by an A-form DNA structure (Llewellyn et al 2009;Scarlett et al 2004). A range of genes were identified in a screen to reveal other, similarly regulated targets and our data suggested that the promoter of one of these genes was probably, like gata2, a target for the Ilf3 transcription factor (Whitley et al 2014), here we have described the identification and characterisation of this gene.…”
Section: Discussionmentioning
confidence: 59%
“…We have previously described a novel promoter type dependent on an A-form DNA structure and identified 86 such potential examples in the Xenopus tropicalis genome (Whitley et al 2014). Aform DNA is a an 'overwound', non-canonical DNA helical structure favoured by dehydration.…”
Section: Cloning Sequencing and Phylogeneticsmentioning
confidence: 99%
“…[ 4 ] After a few years, in 1938, Dr. KK Masani started psychiatric services at JJ Hospital. [ 6 ] This was followed by a once-a-week psychiatry clinic in in the Outpatient Department (OPD) of Patna Medical College Hospital in 1939, under the guidance of Dr. Ghoshal,[ 7 ] and another service by Dr. N S Vahia at KEM Hospital[ 8 ] in the 1940s in Mumbai. Patna Medical College also has the honor of having Professor LP Varma as its first MD psychiatry student in 1941.…”
Section: Resultsmentioning
confidence: 99%
“…These A-form segments can then be specifically recognized by DNA binding proteins during the indirect readout mechanism. Such APSs allow binding of certain transcription factor (TF) binding proteins 21 and could play a role in protein-DNA binding mechanisms. Recently, Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Whitley and coworkers 21 used Basham's trinucleotide solvation free energy method of A/B DNA structure prediction 6 to find A-DNA promoters in the Xenopus tropicalis genome. Owing to the limited applicability of the aforementioned method, we believe that our proposed ML model can be implemented on other genomes to find unknown A-DNA promoter DNA steps a priori.…”
Section: Discussionmentioning
confidence: 99%